Kidney stones and hypertension: population based study of an independent clinical association. Issue 6734 (12th May 1990) - Cappuccio, F P; Strazzullo, P; Mancini, M
Abstract : OBJECTIVE–To test the hypothesis that kidney stone disease is more frequent among hypertensive men when the effect of possible confounders is allowed for. DESIGN–Cross sectional study of a sample of the male working population conducted as part of the 10 year follow up of a nationwide survey of the prevalence of cardiovascular risk factors. SETTING–The Olivetti factory in Pozzuoli, a suburban area of Naples. POPULATION–688 Male workers (87.9% of the male workforce) aged 21-68. INTERVENTIONS–Anthropometric and blood pressure measurements, blood tests, and administration of a detailed questionnaire aimed at detecting a history of urolithiasis. MAIN OUTCOME MEASURES–Prevalence of a history of urolithiasis among normotensive and untreated and treated hypertensive men adjusted for the possible confounding effects of age, body mass index, renal function, and serum urate and total calcium concentrations. RESULTS–Of the 688 participants 509 were normotensive. Of the remainder, 118 had untreated and 61 treated hypertension. The overall prevalence of a history of urolithiasis was 16.3% (112/688). The relative risk of hypertensive subjects having a history of kidney stones was twice that of the normotensive group (odds ratio 2.11; 95% confidence interval 1.17 to 3.81), the risk being higher when only treated hypertensives were considered (odds ratio 3.16; 95% confidence interval 1.75 to 5.71). The prevalence of a history of urolithiasis was 13.4% (68/509) in the normotensive subjects, 20.3% (24/118) in the untreated hypertensives, and 32.8% (20/61) in the treated hypertensives (p less than 0.001). The age adjusted relative risk in treated hypertensive men was higher than that in the normotensive group (Mantel-Haenszel pooled estimate of odds ratio 2.63; 95% confidence interval 2.23 to 3.10). CONCLUSION–An independent clinical association exists between the occurrence of urolithiasis and hypertension. The increased urinary calcium excretion commonly detected in hypertension may be the pathogenetic link.